Učinki slovenske politike državnih pomoči na tržno alociranje proizvodnih dejavnikov - Burger, Anže (IB revija (Ljubljana), 2011)
Do state-aid instruments granted to Slovenian firms distort competition? The authors answer this question using Slovenian Ministry of Finance data on state-aid recipients between 1998 and 2008 and firm-level accounting data from the same period. Results show that state-aid recipients increase their market share and productivity growth in subsequent periods. Despite these findings, the overall effect on allocative efficiency appears to be neutral. The study also investigates the effect of state aid on firm exit rates and finds that government interventions delay the exit of firms receiving aid. In this manner, state-aid grants introduce market distortions and hinder competition.
Keywords: Enterprises; Podjetja; Government aid; Državna pomoč; Competitiveness; Konkurenčnost; Slovenia; Slovenija; gospodarske družbe